Modelamiento y simulación de la adsorción con carbón activa para la recuperación de oro bajo el entorno de Metsim en la concentradora Trebol Dorado S.A.C. - Morán Guillermo, Alex Martín (2023)
The research presented "Modeling and simulation of adsorption with activated carbon for gold recovery under the Metsim® environment in the Trebol Dorado S.A.C concentrator."; Its objective is to build, model and simulate the process known as gold adsorption with activated carbon through the Metsim engineering program, designing part of our flow diagram and sub-processes such as grinding, classification, preparation of cyanide solution, leaching and the same adsorption, therefore the people in charge compiled the information from the concentrator company to carry out their mathematical modeling, diagram construction and then the simulation of the process. A simulation is taken as a tool for making decisions for improvement in a project that can be carried out and this to significantly reduce the time that spreadsheets take, apart from the fact that the interface is made friendly with the equipment it has, as well as the entrances and exits of the currents. The first thing to do is build the flowchart, select the elements or compounds to then configure each current and just start simulating, where said program does not show the procedure but only the results that are required. An important point is that each team has its own configuration; due to a wrong selection of it, it can also cause errors in the runs, for this reason the program will mark it in a different color in the 140 error boxes. It also has the results by means of boxes that are made using the A Programming Language through its keyboard. Finally, the results are obtained where they show the percentage of gold in its recovery in the process treated in the Trebol Dorado S.A.C. concentrator plant.